2013
DOI: 10.1016/j.pain.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular influences on conditioned pain modulation

Abstract: Conditioned pain modulation (CPM) (ie, diffuse noxious inhibitory controls) is characterized by reduced perception of pain caused by intense pain in a remote body area. The conditioning stimuli used to trigger CPM causes pain, but also important cardiovascular responses. Higher blood pressure has been associated with reduced pain sensitivity. Descending pain inhibitory mechanisms such as CPM could be involved in this relationship. We investigated the associations between CPM and cardiovascular responses during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 64 publications
3
46
1
1
Order By: Relevance
“…This was recently demonstrated (Pinto & Polito, ), in which the authors found that exercise with BFR (three sets, 15 reps, 20% 1RM) showed higher values of rating of perceived exertion and blood lactate than traditional exercise (three sets, eight reps, 65% 1RM without BFR). In this sense, the accumulation of lactate creates a more acid environment, which increases BP via muscle metaboreflex (29) and the pain perception caused by the inflated cuff and by the acid environment increases BP due to stimulation of the central nervous system (Chalaye et al ., ). However, data from the present study showed that rating of perceived exertion and blood lactate was higher in the HI‐RE session than the LI‐BFR session.…”
Section: Discussionmentioning
confidence: 97%
“…This was recently demonstrated (Pinto & Polito, ), in which the authors found that exercise with BFR (three sets, 15 reps, 20% 1RM) showed higher values of rating of perceived exertion and blood lactate than traditional exercise (three sets, eight reps, 65% 1RM without BFR). In this sense, the accumulation of lactate creates a more acid environment, which increases BP via muscle metaboreflex (29) and the pain perception caused by the inflated cuff and by the acid environment increases BP due to stimulation of the central nervous system (Chalaye et al ., ). However, data from the present study showed that rating of perceived exertion and blood lactate was higher in the HI‐RE session than the LI‐BFR session.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the rating of perceived exertion seems to be high during LI-BFR exercise due to the discomfort of BFR (Wernbom et al, 2006(Wernbom et al, , 2009. The physical discomfort stimulates the central nervous system and consequently blood pressure (Chalaye et al, 2013). In addition, LI-BFR increases blood lactate (Suga et al, 2009), which raises blood pressure via muscle metaboreflex (Rowell, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings raise the possibility that in response to noxious stimuli, descending pain inhibition may be triggered primarily (or solely) by variations in blood pressure. 5,12 In a subsequent study, the same group observed weak systolic blood pressure changes and weak CPM responses among fibromyalgia patients exposed to a CPT challenge. This, again, raises the possibility of a causal link between blood pressure and descending pain inhibition.…”
Section: Discussionmentioning
confidence: 88%